+0  
 
0
63
1
avatar

https://prnt.sc/po4ymm

 

could please explain step by step?

 Oct 25, 2019
 #1
avatar
+1

Solve for x:
3^(4 x - 5) = 27^(-2 x - 10)

Take the natural logarithm of both sides and use the identity log(a^b) = b log(a):
log(3) (4 x - 5) = 3 log(3) (-2 x - 10)

Divide both sides by log(3):
4 x - 5 = 3 (-2 x - 10)

Expand out terms of the right hand side:
4 x - 5 = -6 x - 30

Add 6 x + 5 to both sides:
10 x = -25

Divide both sides by 10:

x = -5/2

 Oct 25, 2019

10 Online Users

avatar
avatar
avatar